Separated Motherhood: Exploring the experience of mothering premature twins and psychotherapeutic implications - Spiers, James Daniel (European Journal for Qualitative Research in Psychotherapy, 2019)
The experience of giving birth prematurely presents a stressful and challenging time for new mothers, who often spend extensive time with their children in specialist intensive care hospital settings. This can impact the wellbeing of the mother and complicate the process of bonding between mother and child. Despite a high prevalence rate in the UK of prematurity in twin births, very limited research exists on the actual experiences of these mothers.  A hermeneutic phenomenological method is employed to explore the lifeworld experience of becoming a new mother of premature twins. It offers a lived experiential lens that highlights similarities to the contemporary research on mothers of premature singletons, as well as differences within the interpersonal dynamics between a new mother and her two babies that impact on wellbeing.  Semi-structured interviews with three mothers of premature twins elucidates their experience through the transition of ‘becoming’ to ‘being’ a mother. Emotional conflict alienates them from their new motherhood and separates their sense of closeness between their babies.  A fragile sense of coping contains their distress and self-efficacy is drawn from the ability to mother at least one of their twins. The validation of a separated motherhood entwines the haunting of prematurity within their separate relationships with each child.  Implications of this research suggest further exploration of the experiential context is essential to promote a wider inclusion and swift access to appropriate psychological therapies for women presenting to primary care psychological services within their perinatal period.